Variations in the Costs of Pharmacological Treatments According to Exposure to Smoking: A Case Study in Cardiovascular Patients - Vanina Ripari, Nadia (2011)
Several authors have demonstrated an association between the exposure to certain risk factors and the increase in costs of drug treatments for cardiovascular diseases. The present study analyses the pharmacological treatment costs of patients at a Coronary Care unit of dr. Jose Penna Hospital in the city of Bahia Blanca (Argentina) between March 2008 and May 2010. We analyze the daily middle cost variation of pharmacological treatments for ischemic cardiopathy patients with (or without)smoking habits. It has been observed that the cardiopathy isquemic patients with smoking habits face an increased cost associated with/due to higher direct costs in pharmacological treatments than those who were not exposed to smoking. At the same time, the estimated costs for each group of patients show variability depending on being estimated to maximum or minimum prices, as a result of the wide dispersion of prices seen in the pharmaceutical market.